Nontuberculous mycobacteria pathogenesis and biofilm assembly. Issue 1 (March 2015) - Sousa, Sara; Bandeira, Maria; Carvalho, Patricia Almeida; Duarte, Aida; Jordao, Luisa
Abstract Nontuberculous mycobacteria (NTM) are emergent pathogens whose importance in human health has been gaining relevance after being recognized as etiological agents of opportunist infections in HIV patients. Currently, NTM are recognized as etiological agents of several respiratory and extra-respiratory infections of immune-competent individuals. The environmental nature of NTM together with the ability to assemble biofilms on different surfaces plays a key role on their pathogenesis. In the present work the ability of three fast-growing NTM (Mycobacteriumsmegmatis, Mycobacteriumfortuitum and Mycobacteriumchelonae) to persist within a model of human alveolar macrophages was evaluated. Most often human infections with NTM occur by contact with the environment. Biofilms can work as environmental reservoirs. For this reason, it was decided to evaluate the ability of NTM to assemble biofilms on different surfaces. Scanning electron microscopy was used to elucidate the biofilm structure. The ability to assemble biofilms was connected with the ability to spread on solid media known as sliding. Biofilm assembly and intracellular persistence seems to be ruled by different mechanisms.